2007
DOI: 10.1002/cpp.542
|View full text |Cite
|
Sign up to set email alerts
|

How clients with religious or spiritual beliefs experience psychological help‐seeking and therapy: A qualitative study

Abstract: This qualitative study explores the process of help-seeking and therapy among clients with religious or spiritual beliefs. Ten clients who were currently in, or had recently finished, therapy were interviewed. Participants reported using their religious or spiritual beliefs to cope with their psychological problems before and during therapy. Prior to therapy, they worried that secular-based help might weaken their faith. However, the experience of having psychological distress and the process of receiving ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 27 publications
4
73
0
Order By: Relevance
“…Crossley and Salter's 96 study of clinical psychologists' experience of addressing spiritual beliefs in therapy found that, although some practitioners reported a proactive approach, others waited for users to raise spiritual issues on the assumption that if these were significant users would mention them without prompting. Mayers et al 97 found that users were unwilling to disclose such information during assessment because of the fear that it might be evaluated negatively.…”
Section: Discussionmentioning
confidence: 99%
“…Crossley and Salter's 96 study of clinical psychologists' experience of addressing spiritual beliefs in therapy found that, although some practitioners reported a proactive approach, others waited for users to raise spiritual issues on the assumption that if these were significant users would mention them without prompting. Mayers et al 97 found that users were unwilling to disclose such information during assessment because of the fear that it might be evaluated negatively.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, however, religious people have reported that they fear that psychotherapy could undermine their faith (Mayers, Leavey, Vallianatou, & Barker, 2007). Such fears may not be unwarranted.…”
Section: Introductionmentioning
confidence: 94%
“…While much of the evidence is anecdotal there remains a widespread perception of services as religio-phobic among patients and carers (Mayers,Leavey,Vallianatou,& 354 G. Leavey et al Barker, 2007). However, a recent qualitative study of UK psychiatrists and their views on religion suggests that engaging with the religious beliefs of patients is to open a Pandora's box, to be avoided at all costs (Dura-Vila et al, 2011).…”
Section: Ethnicity Religion and Cultural Competencementioning
confidence: 93%
“…Other commentators in psychiatry consider religion to be communally and individually problematic and divisive (Ellis, 1986). However, while psychiatrists tend to be less religious than the general population (Neeleman & King, 1993), there is little evidence that religious patients are penalised or discriminated against because of their beliefs or that they experience relatively worse outcomes than non-religious patients (Mayers et al, 2007). Nevertheless, it is plausible that religiously devout patients may be viewed by secular mental health professionals in a negatively stereotypical way as ignorant, neurotic and superstitious or have concerns about clergy interference in treatment.…”
Section: Ethnicity Religion and Cultural Competencementioning
confidence: 98%